0582 High Rate of OSA among Blacks Using Home-Based WatchPAT Recordings. (27th April 2018) - Kalinowskisi, J; Seixas, A; Chung, A; Chery, K; Richards, S; Chung, D; Jean-Louis, G
Abstract: Introduction: Blacks have greater risk for Obstructive Sleep Apnea (OSA) compared with other racial groups. In two studies using subjective estimates of OSA risk, individuals (n = 1, 035) surveyed in the clinical setting showed a 59% risk of OSA. In the community setting, blacks (n = 120) showed a 43% risk of OSA. In comparison, national data show lower rates (29%). Concerns have arisen that rates of OSA risk among blacks may have been overestimated since subjective measures such as the Apnea Risk Evaluation System (ARES) Questionnaire were used. The purpose of this study was to assess OSA risk among blacks using an objective measure (the WatchPAT). Methods: Data were collected from the Peer Enhanced Education to Reduce Sleep Ethnic Disparities Study, an NIH-funded study assessing effectiveness of peer-delivered sleep health education to black respondents. A sample of 201 individuals (mean age = 47.83 ± 13.57 years; female = 70%) were screened for OSA risk (score ≥6) using the ARES Questionnaire. Those with OSA risk (n = 76) underwent a home-based study using the WatchPAT 200. Individuals wore the WatchPAT during their established bedtime based on data from a week-long sleep diary. A validated algorithm associates arousals with SaO2 measurement to determine respiratory-related arousals, enabling identification of sleep apnea, defined as an Apnea-Hypopnea Index (AHI) ≥5. Results: Of the sample, 60% were employed, 50% reported income less than 20, 000, and 78% completed at least high school; 71% reported insufficient sleep (<7 hours). Of the participants undergoing WatchPAT home studies, 87% had an AHI ≥ 5, the cut-point for OSA. We used logistic regression analyses to ascertain predictors of high rates of OSA, which revealed that age, sex, income and education were not significantly associated with OSA. Conclusion: WatchPAT data indicated that OSA is particularly high among blacks at the community level. Blacks screening positive for OSA should be referred for comprehensive OSA evaluation and treatment. Support (If Any): This research was supported by funding from the NIH (T32HL129953, RO1MD007716 and K07AG052685).